Inside the presidential debates their improbable past and promising future - Minow, Newton N., 1926- (University of Chicago Press, 2008)
This fascinating history offers, for the first time, a genuinely informative inside look into the origins of the presidential debates and the many battles--both legal and personal--that have determined who has been allowed to debate and under what circumstances.